Letter from James Curtis Booth to John Wesley Powell - Booth, James Curtis (1885)
James Curtis Booth (1810-1888) assures James W. Powell (1834-1902), Director of the United States Geological Survey at Washington D.C., that Booth is working diligently on a Geographical Survey of Delaware.
Keywords: Booth, James Curtis, 1810-1888; Powell, John Wesley, 1834-1902; United States Mint; Mint of the United States; Geological Survey (U.S.); Geological surveys